An Ultracompact GRIN‐Lens‐Based Spot Size Converter using Subwavelength Grating Metamaterials. Issue 11 (23rd September 2019) - Luque‐González, José Manuel; Halir, Robert; Wangüemert‐Pérez, Juan Gonzalo; de‐Oliva‐Rubio, José; Schmid, Jens H.; Cheben, Pavel; Molina‐Fernández, Íñigo; Ortega‐Moñux, Alejandro
Abstract: Graded‐index materials offer virtually complete control over light propagation in integrated photonic chips but can be challenging to implement. Here, an anisotropic graded‐index metamaterial, synthesized with fully etched silicon subwavelength structures, is proposed. Based on this material, a spot size converter that expands the transverse electric (TE) mode field profile from a 0.5 µm wide silicon wire waveguide to a 15 µm wide waveguide within a length of only 14 µm is designed. Measured insertion losses are below 1 dB in an unprecedented 130 nm bandwidth, limited by the measurement setup, with full 3D finite‐difference time‐domain (FDTD) simulations predicting a bandwidth in excess of 300 nm. Furthermore, the device is well suited to feed fiber‐to‐chip grating couplers, while requiring a footprint ten times smaller than conventional adiabatic tapers. Abstract : A graded‐index (GRIN) anisotropic metamaterial, synthesized with subwavelength structures, is proposed. Based on this material, a GRIN lens spot size converter from a 0.5 µm silicon wire waveguide to a 15 µm wide waveguide is designed. Measured insertion losses below 1 dB in a 130 nm bandwidth are shown, with simulations predicting a bandwidth in excess of 300 nm.